Interaction of sulfur with phytohormones and signaling molecules in conferring abiotic stress tolerance to plants. (4th May 2018) - Hasanuzzaman, M.; Bhuyan, M. H. M. B.; Mahmud, J. A.; Nahar, K.; Mohsin, S. M.; Parvin, K.; Fujita, M.
ABSTRACT: Sulfur (S) is a macronutrient for the plant, which has an immense role in basic plant processes and regulation of several metabolic pathways. It has also a major role in providing protection against adverse conditions. Sulfur-containing amino acids and metabolites maintain plant cell mechanisms to improve stress tolerance. It interacts with several biomolecules such as phytohormones, polyamines, nitric oxide (NO), and even with other plant nutrients, which can produce some derivatives those are essential for abiotic stress tolerance. Different S derivatives stimulate signaling cascades, for the upregulation of different cellular messengers such as abscisic acid, Ca 2+, and NO. Sulfur is also known to interact with some essential plant nutrients by influencing their uptake and transport, hence, confers nutrient homeostasis efficiencies. This review focuses on how S is interacted with several signaling molecules like NO, glutathiones, phytohormones, hydrogen sulfide, polyamines, etc. This is a concise summary aimed at guiding the researchers to study S-related plant processes in the light of abiotic stress tolerance.